Alternative Therapy of Moringa Leaves and Dates in Reducing Uric Acid Levels - Aris Fitriyani; Maisje Marlyn Kuhu; Esti Dwi Widayanti (GoAcademica Research & Publishing, 2022)
Uric acid, both in the world and in Indonesia, is currently increasing, even at a young age who is still productive, so that it interferes with work productivity due to pain from gout. Gout therapy can be done with medical or non-medical therapy. Non-medical therapy can be carried out with alternative therapies, including the use of Moringa leaves and dates, which until now have not been widely known by the people of Indonesia, so socialization of health education is needed. This study was to determine the difference in knowledge before and after being given health education socialization of alternative gout therapy in Sokaraja District, Banyumas Regency. The method used is quasi-experimental with the control group. The research population is the entire community from the age of teenagers in the Sokaraja District, amounting to 89,184 people. The sampling technique used was random sampling with a total sample of 438 respondents which were divided into 2 groups, namely the intervention group and the control group, each with 219 respondents. The research instrument was a questionnaire. Data analysis using Wilcoxon test. Results There was a difference between the intervention group and the control group before and after the educational outreach intervention for gout alternative therapy with p value = 0.000.